2017
DOI: 10.1584/jpestics.d17-033
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal proportion change of ryanodine receptor mutation (G4946E) in diamondback moth populations

Abstract: This study examined the seasonal proportion change of ryanodine receptor mutation (G4946E) for Plutella xylostella populations using quantitative sequencing. Results showed that the proportions of G4946E generally increased from spring through summer, but then decreased in autumn. Furthermore, the proportions in late autumn were similar to those in early spring of the subsequent year. These results suggest that diamide effectiveness for P. xylostella control in the reference year can be evaluated based on a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In 2017, the proportion of G4946E increased from spring to summer and then decreased toward autumn at both study sites, as observed in 2015 and 2016 15) (Fig. 1).…”
Section: Trap Catches and Seasonal Proportion Changes In G4946e And Isupporting
confidence: 70%
See 4 more Smart Citations
“…In 2017, the proportion of G4946E increased from spring to summer and then decreased toward autumn at both study sites, as observed in 2015 and 2016 15) (Fig. 1).…”
Section: Trap Catches and Seasonal Proportion Changes In G4946e And Isupporting
confidence: 70%
“…In contrast, the proportions of G4946E in P. xylostella populations in some prefectures in Japan were estimated to be greater than the threshold (40%). 15,16) In fact, the detectable proportion of G4946E was found during the survey period at both study sites 15) (Fig. 1).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations